Pharmacokinetic investigation of commercially available edible marijuana products in humans: potential influence of body composition and influence on glucose control - Ewell, Taylor, author; Bell, Christopher, advisor; Hickey, Matthew, committee member; Hamilton, Karyn, committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2021)
Our investigation of five commercially available edible marijuana products containing 10mg of delta-9-tetrahydrocannabinol (THC) aimed to describe the pharmacokinetics of these products, investigate the potential influence of body composition on THC bioavailability, and, based on epidemiological research completed in the last decade, determine if acute marijuana ingestion influences glucose tolerance when compared to a THC-free gummy. We studied seven regular marijuana users. We utilized a single-blind randomized controlled crossover study design in which participants self-administered edible marijuana or a THC-free gummy. Thirty minutes following marijuana ingestion a standard oral glucose tolerance test was initiated via consumption of a 75g glucose drink. There was, at minimum, a four-day washout period between trials. Average time to peak plasma THC concentration ranged from 35 to 90 minutes, and average peak THC concentrations ranged from 3.2 to 5.5 ng/ml. Significant differences between products were identified twenty- and thirty-minutes post-ingestion. Several measures of body composition had significant correlations with plasma THC, although none of these correlations persisted across all products. There were no differences in indices of glycemic control between marijuana products or the THC-free gummy. Following acute edible marijuana ingestion in habitual users, significant differences in THC pharmacokinetics existed between similar products, possibly due to body composition, although glucose control was not impacted. In summary, these data may inform recreational users to the proper dose for marijuana ingestion to achieve the desired outcome and to avoid overdose.
Keywords: edible marijuana; THC; body composition; glucose tolerance